COSMETOLOGINYA AND ADVOKATESSA: THE FUTURE OR THE REALITY OF THE RUSSIAN LANGUAGE? (Philological Studies, 2020)
The article is devoted to feminitives as a linguistic phenomenon studied by gender linguistics. A large number of new feminitives in modern Russian language denotes the relevance of specific names for females, despite the tendency to use masculine words as general words in official speech. The most frequent feminitives are the names of female persons by profession or occupation. The results of a pilot experiment aimed at detecting the use of feminitives when referring to women of certain professions are presented. All data is divided into several groups. The first group consists of professions with a more frequent use of feminitives than names in the masculine grammatical gender. The second group is the one where some of the feminitives are found in dictionaries labeled “colloquial”. The third group includes cases when feminitives exist, but the respondents formed them in a different way using frequency derivational models.
Keywords: feminitives; gender linguistics; profession; word-formation models